Neonatal near Miss and Its Predictors among Neonates Delivered at Debretabor General Hospital, Northern Ethiopia; A Retrospective Analysis - Habtamu Abie Tassew; Fisseha Yetwale Kassie; Muhabaw Shumye Mihret (International Journal of Pediatrics)
Background. In many low-resource countries, the progress of neonatal mortality reduction is very slow. The scenario is notably true in sub-Saharan Africa including Ethiopia. For every neonatal death, there are lots of near missed neonates. Generating evidences on the extent and predictors of neonatal near miss is a key step in neonatal mortality reduction efforts. However, there is limited evidence in this aspect in Ethiopia. Objective. This study is aimed at assessing the proportion of neonatal near miss and associated factors among neonates delivered at Debretabor General Hospital, Northern Ethiopia, 2019. Methods. An institution-based cross-sectional study was conducted on 422 neonates delivered at Debretabor General Hospital from July 1st, 2018, to June 30th, 2019. Both pragmatic and management criteria of definition of neonatal near miss were utilized. A systematic random sampling technique was used to select the cards of the study participants. Data were extracted with structured and pretested checklist, entered in the EpiData, and then exported to SPSS version 20. Both descriptive and analytical procedures have been done. Descriptive statistics such as frequencies and cross tabulations were carried out. The binary logistic regression model was fitted and variables with p value < 0.20 were entered in the multivariable logistic regression model. Both crude and adjusted odds ratios with the corresponding 95% CI were computed. The level of significance has been claimed based on the adjusted odds ratio with 95% CI and its p value of ≤0.05. Results. The proportion of neonates experiencing near miss was obtained to be 32.2% with 95% CI (28, 36). Rural residence (AOR=4.41; 95% CI: 2.57,7.55), incomplete ANC visit (AOR=3.16; 95% CI: 1.90,5.25), primiparous (AOR=2.55; 95% CI: 1.59,4.12), pregnancy-induced hypertension (AOR=3.23; 95% CI: 1.19,8.78), premature rupture of membrane (AOR=4.65; 95% CI: 1.70,12,73), cephalic-pelvic disproportion (AOR=3.05; 95% CI: 1.32,7.01), and antepartum hemorrhage (AOR=4.95; 95% CI: 1.89,12.96) were the independent predictors of neonatal near-miss. Conclusion and Recommendations. The proportion of neonatal near miss was found to be high in the study setting. Most of the determinants of near miss are modifiable obstetric-related factors. Hence, stakeholders need to consider the aforesaid factors while they design interventions.